The “Happy Heart” educational program for changes in health habits in children and their families: protocol for a randomized clinical trial - Minossi, Vanessa (BMC Pediatr, 2015)
BACKGROUND: The prevalence of childhood obesity increased worldwide in recent decades and is associated with risk factors for the development of chronic diseases in adulthood. Strategies for health promotion directed at an early age, with recommendation for healthy habits, can achieve good results. The objective of this study is to evaluate the effectiveness of an innovative, simple and cost effective educational program to improve eating habits, physical activity and the knowledge about healthy habits in children, as well as in their families, as compared to routine outpatient care. METHODS/DESIGN: The study is designed as a randomized clinical trial. Sample size is estimated to include 37 children, aged between 7 and 11 years, and their guardians, randomized for an intervention or a control group. The intervention will consist of 11-weekly group meetings of nutritional education and distribution of explanatory material, with orientation about healthy food and family habits and physical activity. Recreational, simple and low cost resources, carefully designed for the presentation of contents to the children and parents, will be used in all meetings. The control group will receive standard outpatient care based in individual clinical practice guidelines. The primary outcomes will be changes in dietary habits, knowledge and physical activity of children and adults. The secondary outcomes will be changes of body mass index, waist circumference, systolic and diastolic blood pressure and laboratory tests, in children and adults. DISCUSSION: The Happy Heart Study offers a playful and low-cost approach for the prevention and control of obesity and cardiovascular disease in children. Although this program is being planned for implementation in Brazil, the method can be adapted to many other countries. REGISTRY OF PROTOCOL: Protocol registered on the site ensaiosclinicos.gov.br: RBR-8ttw64.